Analysis of COVID-19 crisis-related building energy retrofit incentives in Italy - Rosa Francesca De Masi; Valentino Festa; Antonio Gigante; Silvia Ruggiero; Giuseppe Peter Vanoli (Energy Reports, 2022)
The advent of the COVID-19 pandemic led to an economic crisis of the construction industry and to an increasing of energy consumption in the residential sector for all the world. The European Union highlights the crucial role of building sector for both energy gains and economic growth, defining a “Renovation Wave” plan combining regulation, financing and technical support with the aim of greening the buildings, creating jobs and improving lives. In Italy a great support mechanism for energy refurbishment of existing buildings has been launched by means of tax deduction of 110% over 5 years. The present study aims to analyze this new funding mechanism, under energy, environmental and economic point of views. By means of a real case study, representative of highly widespread southern Italy HVAC-building system, it will be highlighting advantages and contradictions of the incentive mechanism developed, proposing possible future improvements. It is found that, if on one hand, the best refurbishment measure under energy/environmental point of view is the external insulation, windows replacement, electric heat pump and PV-system installation, with a global not renewable performance index reduction of 81%, on the other hand it is not the best solution considering the cost/saving ratio.